BUSINESS PROJECT BEAUTY SALON FOR WOMEN AND CHILDREN IN MAJALENGKA REGENCY - Tasya Rahmania Khairunnisa Hamidah; Keni Kaniawati (LPPM STIE Muhammadiah Bandung, 2026)
The Hibiscus Salon is a women-and-children beauty MSME in Majalengka Regency. This project evaluates the current business model and formulates development strategies to improve competitiveness and deliver personalized, hygienic, and family-friendly services. The approach combines SWOT–TOWS analysis, Design Thinking to capture customer needs and translate them into solutions, and Agile-inspired execution to ensure iterative and adaptive implementation. The findings indicate that the salon’s key strengths lie in its differentiated concept and customer experience. Development priorities include strengthening digital branding, standardizing SOPs, enhancing human resource capability, improving financial recordkeeping, and accelerating legal compliance and certification to support sustainable growth.